Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Proyek Pembangunan Jembatan Jalan Trans Sulawesi - Kahfi , Restu Aji Nur; Rosita, Rosita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Every construction project in Indonesia is required to implement an Occupational Safety and Health Management System (SMK3), so SMK3 evaluation is crucial to ensure the safety and health of workers. This study aims to determine the level of understanding of SMK3 from the perspective of project managers and employees. The research methodology consists of direct field observation combined with questionnaires and interviews with employees and project managers. With a project management score of 83.33% and a worker score of 62.62%, the results indicate that both project management and workers are in the moderate group. This study offers ways to improve the implementation of SMK3 and conduct additional outreach regarding the importance of health and safety in the workplace.